The neural substrates of subjective time dilation - Wittmann, Marc; Van Wassenhove, Virginie; Craig, Bud; Paulus, Martin P. (Frontiers in Human Neuroscience, 2010)
An object moving towards an observer is subjectively perceived as longer in duration than the same object that is static or moving away. This 'time dilation effect' has been shown for a number of stimuli that differ from standard events along different feature dimensions (e.g. color, size, and dynamics). We performed an event-related functional magnetic resonance imaging (fMRI), while subjects viewed a stream of five visual events, all of which were static and of identical duration except the fourth one, which was a deviant target consisting of either a looming or a receding disc. The duration of the target was systematically varied and participants judged whether the target was shorter or longer than all other events. A time dilation effect was observed only for looming targets. Relative to the static standards, the looming as well as the receding targets induced increased activation of the anterior insula and anterior cingulate cortices (the “core control network”). The decisive contrast between looming and receding targets representing the time dilation effect showed strong asymmetric activation and, specifically, activation of cortical midline structures (the “default network”). These results provide the first evidence that the illusion of temporal dilation is due to activation of areas that are important for cognitive control and subjective awareness. The involvement of midline structures in the temporal dilation illusion is interpreted as evidence that time perception is related to self-referential processing.